Chitosan particle stabilized Pickering emulsion/interleukin-12 adjuvant system for Pgp3 subunit vaccine elicits immune protection against genital chlamydial infection in mice - Shu, Mingyi; Zhao, Lanhua; Shi, Keliang; Lei, Wenbo; Yang, Yewei; Li, Zhongyu (Frontiers in Immunology, 2022)
Considering the shortcomings in current chlamydia control strategies, a major challenge in curtailing infection is the implementation of an effective vaccine. The immune response induced by C. trachomatis plasmid encoded Pgp3 was insufficient against C. trachomatis infection, which requiring adjuvant applications to achieve the robust immune response induced by Pgp3. There is increasingly promising in developing adjuvant system relying on delivery potential of Pickering emulsions and the immunomodulatory effects of interleukin (IL)-12. Here, owing to the polycationic nature, chitosan particle tended to absorb on the oil/water interphase to prepared the optimized chitosan particle-stabilized Pickering emulsion (CSPE), which was designed as delivery system for Pgp3 protein and IL-12. Our results showed that the average droplets size of CSPE was 789.47±44.26 nm after a series of optimizations and about 90% antigens may be absorbed by CSPE owing to positively charged surface (33.2±3mV), and CSPE promoted FITC-BSA proteins uptake by macrophages. Furthermore, as demonstrated by Pgp3-specific antibody production and cytokine secretion, CSPE/IL-12 system enhanced significantly higher levels of Pgp3-specific IgG, IgG1, IgG2a, sIgA and significant cytokines secretion of IFN-γ, IL-2, TNF-α, IL-4. Similarly, vaginal chlamydial shedding and hydrosalpinx pathologies were markedly reduced in mice immunized with Pgp3/CSPE/IL-12. Collectively, vaccination with Pgp3/CSPE/IL-12 regimen elicited robust cellular and humoral immune response in mice resulting in obvious reduction of live chlamydia load in the vaginal and inflammatory pathologies in the oviduct, which further propelling the development of vaccines against C. trachomatis infection.